A cysteine residue in the third membrane-spanning segment of the human D2 dopamine receptor is exposed in the binding-site crevice. - Javitch, J A (1994)
The binding site in G-protein-linked neurotransmitter receptors is formed among their membrane-spanning segments. Because the binding site is in the plane of the bilayer and is accessible to charged, water-soluble agonists, it must lie in a crevice open to the extracellular, aqueous medium. Information about the structure of these receptors can be obtained by identifying the residues in the membrane-spanning segments which face this water-filled crevice. Human D2 dopamine receptor was expressed in human embryonic kidney 293 cells. Small, charged, sulfhydryl-specific methanethiosulfonate (MTS) derivatives irreversibly inhibited the binding of the D2-specific antagonist [3H]YM-09151-2 to these cells. The highly polar MTS derivatives should react with cysteine sulfhydryl groups only at the water-accessible surface of the receptor, which includes the surface of the binding-site crevice. In contrast, these reagents will have little access to sulfhydryls facing the lipid bilayer or buried in the protein interior. Positively charged MTS reagents irreversibly inhibited binding several hundredfold faster than a negatively charged MTS reagent, consistent with the affinity of the binding site for positively charged dopamine agonists and antagonists. Furthermore, both agonists and antagonists of the D2 receptor protected against irreversible inhibition by the MTS reagents. To identify the susceptible cysteine, we mutated, one at a time, five transmembrane and two extracellular cysteine residues to serine. Only the mutation of Cys118 to serine decreased the susceptibility of antagonist binding to irreversible inhibition by the MTS reagents. Thus, Cys118, a residue in the middle of the third membrane-spanning segment, is exposed in the D2 receptor binding-site crevice.